Top answers

Maths
All levels

How do you factorise a quadratic expression using the formula

To factorise an expression of the formax2+bx+c We use the formulaX=(-b+/- (b^2-4ac)^(1/2))/2aExample:Factorise 3X2+2X+-1So here a=3 b=2 c=-1From the formula we get X=1/3 and X=-1And ...

Answered by Kaitrin S. Maths tutor
2520 Views

solve for x, in the form x = loga/logb for 2^(4x - 1) = 3^(5-2x) (taken from OCR June 2014 C2)

We can take logs of both sides straight away, and using the log rule that alogb = log(b^a)So(4x-1) log(2) = (5 - 2x) log(3)We can expand the bracketsso (4x)log(2) - log(2) = 5log(3) - 2xlog(3)We can group...

Answered by Ellie N. Maths tutor
7511 Views

Calculate y=4x-6 when x=3

Firstly we have an equation y=4x-6. We are given that x=3 and we want to find y. What we must do is substitute x=3 into the equation to get y: y=4(3)-6 =6

Answered by Sinan U. Maths tutor
3432 Views

Expand and simplify (3x^2 + 2)(2x + 5) – 6x(x^2 – 3)

First, multiply out 6x(x^2 - 3) so that it becomes – 6x^2 – 18xThen, multiply (3x^2 + 2) and (2x + 5) so that it becomes 6x^3 + 15x^2 + 4x + 10Add the two results above: 6x^3 + 15x^2 + 4x + 10 – 6x^3 – 18...

Answered by Ancel B. Maths tutor
7391 Views

The curve C has the equation y=((x^2+4)(x-3))/2*x where x is not equal to 0 . Find the tangent to the curve C at the point where x=-1 in the form y=mx+c

Firstly we need to expand out y into a series of terms to make it easier for us to compute the derivative . You multiply out the brackets to get y=(x3-3x2+4x-12)/2x then we divide ea...

Answered by Ellie M. Maths tutor
11148 Views

We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences